2020
DOI: 10.1155/2020/5602163
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Drying‐Wetting Cycles on Engineering Properties of Expansive Soils Modified by Industrial Wastes

Abstract: The swelling properties of expansive soils can be reduced by the addition of modifiers. Nevertheless, the performance deterioration after modification occurs when weathering for a long term. Therefore, in this study, the effect of drying-wetting cycles on swelling behaviour and compressibility of modified expansive soils with the iron tailing sand and calcium carbide slag has been investigated. The swelling potential initially increases and subsequently decreases with the increasing number of cycles, reaches t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Some scholars have improved the expansive soil with other materials (such as slag, fly ash, and lime) to reduce its cracks. The final results show the effectiveness of these methods [ 23 , 24 , 25 ]. Coal gangue contains more mineral components, such as low hydrophilic kaolinite and illite.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some scholars have improved the expansive soil with other materials (such as slag, fly ash, and lime) to reduce its cracks. The final results show the effectiveness of these methods [ 23 , 24 , 25 ]. Coal gangue contains more mineral components, such as low hydrophilic kaolinite and illite.…”
Section: Discussionmentioning
confidence: 99%
“…An appropriate amount of lignin can be filled in the soil pores to make the soil particles more closely connected, so as to improve the stability of expansive soil. Chu et al [ 24 ] studied the effects of drying–wetting cycles on the expansion behavior and compressibility of iron tailing sand and calcium carbide slag-modified expansive soil. The micro-pore structure of soil samples was analyzed by the mercury injection method.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas the study area falls under inorganic clays of high plastic clay soil except the test pits TP10 and TP11, which is inorganic silt (MH) as per Unified Soil Classification System. In which all test pits having liquid limits values more than fifty revealed that the soils in the area are presented by high plasticity and expansiveness, which are fulfilling the requirements of the specified practices of expansive properties [31].…”
Section: Soil Classificationsmentioning
confidence: 91%
“…The effectiveness of expansive soil modification materials under adverse environmental influences, such as wet-dry cycles and freeze-thaw cycles, should also be considered. Mixtures of octadecyl trimethyl ammonium chloride and Potassium chloride, iron tailing sand and calcium carbide slag, polypropylene fiber and silica fume, and nano-silica and electric arc furnace slag still exhibit good modification effects of expansive soil after wet-dry or freeze-thaw cycles [167][168][169][170].…”
Section: Materials Modification Methodsmentioning
confidence: 99%